THE ISLAMIC VIEW TOWARD PEOPLE WITH DISABILITIES IN EDUCATION POLICY IN INDONESIA - Gustiana Yuantini (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
Abstract: Islam views a person before Allah. It is not because of the physical, but the taqs. Thus, individual has equal rights and obligations in this case, education. Along with the statements within Statute Number 20 in 2003, it stated that